Salvianolic Acid B Improves Mitochondrial Function in 3T3-L1 Adipocytes Through a Pathway Involving PPARγ Coactivator-1α (PGC-1α) - Pan, Yanyun; Zhao, Wenjing; Zhao, Dandan; Wang, Chaoyang; Yu, Na; An, Tian; Mo, Fangfang; Liu, Jiaxian; Miao, Jianan; Lv, Bohan; Gu, Yujie; Gao, Sihua; et al. (Frontiers in Pharmacology, 2018)
Purpose: Mitochondrial dysfunction in adipose tissue has emerged as key to the development of obesity and diabetes. Salvianolic acid B (SalB) is a water-soluble ingredient derived from Salvia miltiorrhiza that has been shown to possess potential anti-obese and anti-diabetic activities. However, the cellular mechanism of SalB on mitochondrial function with respect to these metabolic disorders has not been elucidated. Therefore, we aim to investigate the effects of SalB on mitochondrial function in 3T3-L1 adipocytes and analyze the underlying molecular mechanism. Methods: The effects of SalB on adipocyte differentiation, glucose uptake and glycerol release were evaluated in 3T3-L1 adipocytes. Differentiated adipocytes were treated with SalB (50 μM) with or without PPAR antagonist (GW9662, 20 μM) for 48h, and mitochondrial oxygen consumption rate (OCR) as well as extra cellular acidification rate (ECAR) were assessed using an XF Extracellular Flux Analyzer. The mitochondrial distribution of adipocytes was assessed using Mito Tracker Green (MTG) and observed under a fluorescent microscope. In addition, the mRNA expression levels of peroxisome proliferators-activated receptor / (PPAR/), CCAAT/enhancer binding protein (C/EBP), Nuclear respiratory factor 1/2 (NRF1/2), Uncoupling protein 2 (UCP2) and phosphofructokinase 2/fructose-2, 6-bisphosphatase 2 (PFKFB2) were detected by RT-PCR. Finally, changes in the protein levels of peroxisome proliferators-activated receptor γ coactivator-1α (PGC-1α) were determined by western blotting and immunofluorescence analysis. Results: Treatment with SalB increased glucose uptake and mitochondrial respiration, reduced glycerol release, and promoted adipocyte differentiation by increasing mRNA expression of adipogenic transcription factors including PPAR, C/EBP and PPAR. Furthermore, SalB enhanced adipocytes mitochondrial content, mitochondrial respiration and glycolysis capacity, which had been attenuated by GW9662 treatment through the increased expression of PGC-1α. Conclusion: Our results provide novel insights into the role of PGC-1α and mitochondria as probable mediators of SalB activity in the regulation of adipocyte differentiation in 3T3-L1 adipocytes.